The economic theory of product differentiation - Beath, John (Cambridge University Press, 1990)
There are few industries in modern market economies that do not manufacture differentiated products. This book provides a systematic explanation and analysis of the widespread prevalence of this important category of products. The authors concentrate on models in which product selection is endogenous. In the first four chapters they consider models that try to predict the level of product differentiation that would emerge in situations of market equilibrium. These market equilibria with differentiated products are characterised and then compared with social welfare optima. Particular attention is paid to the distinction between horizontal and vertical differentiation as well as to the related issues of product quality and durability. This book brings together the most important theoretical contributions to these topics in a succinct and coherent manner. One of its major strengths is the way in which it carefully sets out the basic intuition behind the formal results. It will be useful to advanced undergraduate and graduate students taking courses in industrial economics and microeconomic theory